Civic empowerment in an age of corporate greed - Lorenz, Edward C. (Michigan State University Press, 2012)
"A thought-provoking investigation of an urgent issue facing American communities today, Edward C. Lorenz's book examines the intersection of corporate irresponsibility and civic engagement. At the heart of this case study is a group of firms responsible for seven of the most contaminated Superfund sites in the United States, the largest food contamination accident in U.S. history, stunning stock and financial manipulations, and a massive shift of jobs offshore. In the face of these egregious environmental, employee, and investor abuses, several communities impacted by these firms organized to confront and combat failures in corporate and bureaucratic leadership, winning notable victories over major financiers, lobbyists, and indifferent or ineffective government agencies. A critical analysis of public and private leadership, business and economic ethics, and civic life, this book concludes with a stirring blueprint for other communities facing similarly overwhelming opposition"--